«Fragility» as a predictor of bleedings in elderly patients with atrial fibrillation taking direct oral anticoagulants - M. A. Gabitova; P. M. Krupenin; A. A. Sokolova; D. A. Napalkov; V. V. Fomin (Сибирский научный медицинский журнал, 2020)
The purpose of the study is to assess the contribution of senile asthenia level to hemorrhagic complications quantity in elderly patients with atrial fibrillation (AF) taking direct oral anticoagulants (DOAC).Material and methods. Elderly patients >75 y.o. with AF taking dabigatran, apixaban or rivaroxaban in full or reduced dosages and without special features of bleeding (such as double and triple antithrombotic therapy) were included in the study. If a patient was under anticoagulants before the study (but not earlier than one became 75 y.o.), this experience was also analyzed. All bleedings during the first 18 months of anticoagulating were taken in mind. Patients in different DOAC groups were comparable in age and concomitant pathology. The «fragility» index was evaluated at the stage of inclusion in the study; an adapted Rockwood scale was used.Results and discussion. 102 patients with AF >75 y.o. taking dabigatran, apixaban or rivaroxaban in dosages corresponding to the instructions were included in the study. During the analyzed period, 19 small clinically significant hemorrhagic events that did not require hospitalization or cancellation of DOAC were recorded. Patients with and without bleeding in anamnesis were significantly differed only by «fragility» index score (р = 0,001). The differences between concomitant pathology level which are mentioned in scale, is also not statistically significant. The average age of patients with and without bleeding anamnesis was not also significantly different (p = 0.12). In the future, it is advisable to continue the study using several scales for assessing the severity of the «fragility» index. Thus, it is advisable to calculate the «fragility» index in patients >75 years of age with AF taking DOAC.